Resilience to climate-induced food insecurity in Nigeria: a systematic review of the role of adaptation strategies in flood and drought mitigation - Timothy A. Akinkuolie; Timothy A. Akinkuolie; Timothy O. Ogunbode; Aruna O. Adekiya (Frontiers in Sustainable Food Systems)
IntroductionClimate change presents weighty challenges globally, with Nigeria particularly vulnerable to its multifaceted impacts. This review explores the effects of climate change-induced droughts and floods on food security in Nigeria, where agriculture is central to economic stability and livelihoods.MethodsThe analysis integrates a comprehensive metadata evaluation, identifying trends, thematic gaps, and regional disparities in existing research. A systematic review of 2,500 publications, following PRISMA criteria, narrowed the focus to 450 studies, with 104 high-quality studies undergoing in-depth analysis.ResultsMetadata analysis revealed an increase in research interest post-2010, a lack of longitudinal studies, and an underrepresentation of semi-arid northern regions in the literature. Findings indicate a growing threat to Nigeria’s food security, as frequent flooding destroys infrastructure, erodes topsoil, and reduces agricultural productivity, leading to lower food output and increased costs. At the same time, droughts, particularly in the semi-arid north, drastically reduce crop yields and worsen food insecurity by depleting vital water resources. These challenges disproportionately affect smallholder farmers and pastoral communities, waning poverty and hunger.DiscussionThe review highlights the complexity of Nigeria’s food insecurity, shaped by factors such as geography, socioeconomic status, and adaptive capacity. Despite advancements in adaptation strategies, issues like fragmented policies and inadequate infrastructure continue to hinder effective responses. However, the review identifies key opportunities to enhance food security and resilience, including greater stakeholder engagement, increased investment in climate adaptation, and the use of digital technologies. By addressing these challenges and leveraging the opportunities, Nigeria can build a more resilient and sustainable food system capable of withstanding the increasing threats posed by climate change.